Logics of Extraction and of the Valorisation of Culture: The Role of Post-extraction Investment in the Creation of Inequality in China - Ryan Parsons (Revue Internationale de Politique de Développement)
What sort of social and economic arrangements are enabled by an extractive economy and its successors? How are patterns of social stratification influenced by these processes? Drawing on ethnographic evidence collected in a tourist destination town in Yunnan that is surrounded by iron mines, I argue that the underlying logics of extractivism persist into the development of a service sector economy (in this case, tourism). The specific case documents economic and social change in a community being reshaped by an emergent cultural tourism industry. New logics of extractivism are motivated by an assumption that peripheral capital is raw and unchanging and exists to be processed, monetised, and consumed by core elites. Even as the makeup of economic sectors change, the national periphery continues to be a site of raw resources to be extracted and valorised by elites and other stakeholders from urban cores. The effect of this extractive tourism industry is to flatten, ossify, and ‘legibilise’ culture in ways that prioritise performance and experience over the agency of local people. The resulting reformation of cultural practice creates new forms of inequality, here marked by gender and ethnicity.